Potential Legal Challenges to President Rodrigo Duterte's Decision to Withdraw the Philippines from the Roman Statute - Balisacan, Ryan Hartzell C. (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
I. Background and Content; II. Discussion and Analysis; III.
Keywords: Crimes against humanity; Drugs and crime